The course of bullous pemphigoid against the background of vaccination against a new coronavirus infection (COVID-19) - Andrey A. Martynov; Anna V. Vlasova (State Scientific Center of Dermatovenereology and Cosmetology, 2021)
The article describes a clinical case of vaccination with the drug "Kovivac" of a patient of an older age group with an established diagnosis of bullous pemphigoid. Scientific data on the prevalence of bullous dermatoses in the Russian Federation (true pemphigus, Lever's bullous pemphigoid, Dhring's herpetiformis dermatitis) are presented. There is a good tolerance of the Kovivac vaccine in a patient suffering from bullous pemphigoid, which allows vaccination, in fact, without interrupting patients from their daily activities and without diverting the resources of the healthcare system to unreasonable inpatient care. The decision to vaccinate should be made on the basis of data on the available indications / contraindications for drugs, taking into account the individual anamnestic data of patients. In addition, it should be borne in mind that until now, all links of the infectious process caused by SARS-CoV-2 have not been fully studied. In this regard, before vaccination, patients must be informed of the need to comply with the anti-epidemic measures recommended for the prevention of coronavirus infection (COVID-19), even after full vaccination, as well as dynamic observation by specialist doctors.